Peningkatan Hasil Belajar Menulis Teks Report Melalui Teknik Error Analysis Pada Mahasiswa Stifar Yayasan Universitas Riau - Jismulatif ' (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2012)
The aim of this classroom action research is to improve the student’s ability inwriting report texts. The sample respondents were 40 students of STIFAR engaged inEnglish subject. Before the treatment was conducted, the sample was given pre-test and afterthe treatment, post-test was also held. The result of observation (52, 95%) and mean score oftest of cycle I (62, 30) cannot full fill the minimum criteria applied, 70. The action iscontinued at cycle II by continuing to apply Error analysis activities at cycle I and give moremotivation and support to be more active in doing Error analysis activities. Beside that,special guidance for those who need is also provided outside class. In fact, there is a highincrease of observation and test result at cycle II compare to the increase in cycle I. Thestudent’s ability in doing Error analysis activities becomes 77, 22 % and the mean score ofthe test is 75,3 The result this research shows that the criteria applied has been achieved andthis means that Error Analysis strategy is very active to increase student’s ability incomprehending writing text report in English.